Corrigendum to “Pathways to conventional and radical climate action: The role of temporal orientation, environmental cognitive alternatives, and eco-anxiety” [Glob. Environ. Change 87 (2024) 102886] - Charlie R. Pittaway; Kelly S. Fielding; Winnifred R. Louis (Global Environmental Change, 2026)

Who do we trust on climate change, and why? - Sarah MacInnes; Matthew J. Hornsey; Christian Bretter; Samuel Pearson; Kelly S. Fielding; David Bersoff (Global Environmental Change, 2026)

Evaluating environmental health communication: The readability of factsheets about per- and polyfluoroalkyl substances (PFAS) - Carla R. Magi-Prowse; Kelly S. Fielding; Kevin V. Thomas; Kylie Morphett (International Journal of Hygiene and Environmental Health, 2026)

Can Instagram contribute to the wellbeing and flourishing of Australian farming women in the midst of climate challenges? - Amy R. Samson; Kelly S. Fielding; Natalie Collie (Journal of Rural Studies, 2025)

Eliciting diverse perspectives to prioritize community actions for biodiversity conservation - Angela J. Dean; Kelly S. Fielding; Liam D. G. Smith; Emma K. Church; Kerrie A. Wilson (Conservation Biology, 2025)
Communities have a strong role in protecting biodiversity. In addition to participation in restoration, a range of actions in the public or private sphere may support biodiversity. Despite this, there is a lack of clarity about what actions should be prioritized for behavior change campaigns. We developed and applied a method to prioritize community actions for biodiversity conservation that incorporates an expert‐based assessment of impact and a community‐informed measure of the likelihood of uptake. In stage 1, experts ( n = 143) completed a survey that quantified the relative impact of actions based on best–worst scaling of perceived impact. In stage 2, surveyed community members ( n = 3200) ranked the likelihood of adopting actions based on the ease or difficulty of performing each action, and the opportunity for change based on the proportion of respondents not yet engaging in each behavior. Experts gave the following actions the highest ranking for impact: voting for the environment (first), participating in restoration in ecological priority areas (second), and purchasing and protecting remnant bushland (third). When considering the disciplinary background and institutional background of experts, voting and participating in restoration activities remained in the upper ranked options. However, there was some divergence between these groups. For example, reducing beef consumption was ranked third by university‐based experts but ranked 28th by experts based in state government. Overall, community members ranked the following behaviors as most likely to be adopted: following quarantine laws (first), reducing plastic use (second), and managing pets (third). Top likelihood ranking of actions was minimally affected by community characteristics (nature relatedness, gender, location). Integrating these findings, the action ranked most favorably for impact, likelihood, and opportunity was participating in restoration. Choosing actions for behavior change campaigns requires consideration of the entire social–ecological system—from social factors that enable or constrain adoption to the ecological impact of actions across relevant social and ecological contexts.

Landholders’ intentions to engage in private land conservation agreements under climate risk - Nanda Kaji Budhathoki; Kelly S. Fielding; Jonathan R. Rhodes; Carla L. Archibald; Daniel Lunney; James Brazil-Boast; Scott Benitez Hetherington; James A. Fitzsimons; Md Sayed Iftekhar (Journal of Environmental Management, 2025)

Media ownership and coverage patterns of established, disruptive, and unconventional climate advocacy groups - Robyn E. Gulliver; Xiongzhi Wang; Winnifred R. Louis; Kelly S. Fielding; Rebecca M. Colvin (Climatic Change, 2025)
Groups advocating on climate and environmental issues often seek to obtain media coverage to increase public awareness of their cause, yet comparatively little is understood about the factors influencing the volume and content of that coverage. This study investigates the quantity and characteristics of media coverage of climate advocacy groups through a mixed-method analysis of 17,380 Australian media articles published between 2017–2022. Four types of advocacy groups were the focus: ‘Established’ groups (large professionalised environmental groups); ‘Disruptive’ groups (the greatest use of civil resistance tactics); and two types of what we call ‘Unconventional advocates’ – those who advocate for action on climate change but from a social identity position that is either typically not associated with climate action (‘Role-based unconventional advocates’, such as parents or doctors) or has a history of conflict with climate or other environmental causes and environmentalists (‘Conflict-spanning unconventional advocates’, such as farmers and political conservatives). Findings indicate that linguistic cues associated with conflict, achievement, and emotional sentiment differed significantly according to the advocacy group type and media ownership. While Established groups gained the greatest volume of coverage, Disruptive groups attracted the highest conflict language and lowest achievement language, particularly in outlets published by News Corp (the Murdoch owned media company). Meanwhile, conflict-spanning unconventional advocates received coverage using language with the lowest levels of conflict and highest levels of achievement. Our findings highlight the potential for new types of climate advocates to gain comparative sympathetic media coverage and potentially expand the social basis of support for climate action.

Is Australia's urban-regional schism on climate reality or rhetoric? - R.M. Colvin; Frank Jotzo; Kelly S. Fielding (Journal of Rural Studies, 2024)

Pathways to conventional and radical climate action: The role of temporal orientation, environmental cognitive alternatives, and eco-anxiety - Charlie R. Pittaway; Kelly S. Fielding; Winnifred R. Louis (Global Environmental Change, 2024)

Public opinion about solar radiation management: A cross-cultural study in 20 countries around the world - Nadja Contzen; Goda Perlaviciute; Linda Steg; Sophie Charlotte Reckels; Susana Alves; David Bidwell; Gisela Böhm; Marino Bonaiuto; Li-Fang Chou; Victor Corral-Verdugo; Federica Dessi; Thomas Dietz; et al. (Climatic Change, 2024)
Some argue that complementing climate change mitigation measures with solar radiation management (SRM) might prove a last resort to limit global warming to 1.5 °C. To make a socially responsible decision on whether to use SRM, it is important to consider also public opinion, across the globe and particularly in the Global South, which would face the greatest risks from both global warming and SRM. However, most research on public opinion about SRM stems from the Global North. We report findings from the first large-scale, cross-cultural study on the public opinion about SRM among the general public ( N = 2,248) and students ( N = 4,583) in 20 countries covering all inhabited continents, including five countries from the Global South and five ‘non-WEIRD’ (i.e. not Western, Educated, Industrialised, Rich, and Democratic) countries from the Global North. As public awareness of SRM is usually low, we provided participants with information on SRM, including key arguments in favour of and against SRM that appear in the scientific debate. On average, acceptability of SRM was significantly higher in the Global South than in the ‘non-WEIRD’ Global North, while acceptability in the ‘WEIRD’ Global North was in between. However, we found substantial variation within these clusters, especially in the ‘non-WEIRD’ Global North, suggesting that countries do not form homogenous clusters and should thus be considered individually. Moreover, the average participants’ views, while generally neither strong nor polarised, differed from some expert views in important ways, including that participants perceived SRM as only slightly effective in limiting global warming. Still, our data suggests overall a conditional, reluctant acceptance. That is, while on average, people think SRM would have mostly negative consequences, they may still be willing to tolerate it as a potential last resort to fight global warming, particularly if they think SRM has only minor negative (or even positive) impacts on humans and nature.

Investigating how economic and national identity loss messages impact climate change policy support - Anna Klas; Edward J. R. Clarke; Kelly Fielding; Matthew Mackay; Susanne Lohmann; Mathew Ling (Climatic Change, 2022)

Non-climatic stressors constraining adaptation to drought in rice-farming communities in the Philippines - Jaime Albarillo Manalo IV; Elske van de Fliert; Kelly Fielding (Climate and Development, 2022)

The relationship between country and individual household wealth and climate change concern: the mediating role of control - Céline Nauges; Sarah Ann Wheeler; Kelly S. Fielding (Environment, Development and Sustainability, 2021)

Achieving conservation impact by shifting focus from human attitudes to behaviors - Danielle Nilsson; Kelly Fielding; Angela J. Dean (Conservation Biology, 2020)
Attitudes have been a commonly used psychological measure of program effectiveness in conservation social science research. The major limitation of this approach is that attitudes do not always translate into behavior and therefore may not provide an accurate assessment of program success. Given that achieving conservation goals generally relies on understanding and changing human behavior, we argue for the need to assess behavior rather than attitudes as an indicator of conservation outcomes. Psychological theory shows that attitudes and behavior are distinct, but related, concepts. Measuring conservation behaviors involves identifying the target behavior or behaviors and the optimal time to measure and then selecting the most appropriate method of measurement (i.e., direct observation, objective indicators, self‐reported behavior, and behavioral intentions) that considers the strengths and weaknesses of each approach. We call for conservation programs to focus on influencing behavior rather than attitudes alone and encourage conservation practitioners and researchers to collect high‐quality behavioral data to more effectively inform policy and programs.

Using ingroup messengers and ingroup values to promote climate change policy - Kelly S. Fielding; Matthew J. Hornsey; Ha Anh Thai; Li Li Toh (Climatic Change, 2020)

Comparing Public Perceptions of Alternative Water Sources for Potable Use: The Case of Rainwater, Stormwater, Desalinated Water, and Recycled Water - Kelly S. Fielding; John Gardner; Zoe Leviston; Jennifer Price (Water Resources Management, 2015)

The expression of neuregulin and erbB receptors in human skeletal muscle: effects of progressive resistance training - Nathan K. LeBrasseur; Kelly C. Mizer; Jascha D. Parkington; Douglas B. Sawyer; Roger A. Fielding (European Journal of Applied Physiology, 2005)